Accounting Information System and Internal Control as Determinants of Financial Statement Quality - Wulandari, Niluh Merthi; Usman, Ernawaty; Yamin, Nina Yusnita; Pakawaru, Muhammad Ilham (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Good governance and public confidence require high-quality financial reporting. This research is to see the influence of AIS, and Internal control against financial reporting system of quality in Public Health Center (Puskesmas) in Kabupaten Parigi Moutong. The study relies on a quantitative method of research with sample data coming from 72 participants who are the heads of centers, administrative head and treasurer. The data were analyzed by multiple regression analysis with F-test, t-test, and coefficient of determination (R²). The finding indicates that both AIS and Internal Control significantly affect financial reporting quality (F = 53.245; Sig. 0.000). Part of Internal Control has positively and significantly influence (t = 7.378; Sig. 0.000) and AIS has no effect (t = 0.417; Sig. 0.678). The R² value (0.607) is equal to the proportion of both variables that account for 60.7% from financial report quality variance. These observations validate that enhancing internal controls is the main approach to reliable transparent and accountable financial reports among Public Health facilities.